Transformative Care-Based Supervision and Sustainable Teacher Performance - Shofwani, Siti Aniqoh; Raharjo, Tri Joko; Fakhruddin, Fakhruddin; Arief, Sandy; Taufikin, Taufikin (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2026)
This study aims to examine the effectiveness of Transformative Care-Based Supervision, which integrates academic, collaborative, and clinical supervision, in strengthening teacher competence, psychological well-being, and sustainable performance. Employing a quantitative explanatory research design, the study was conducted among the population of senior high school teachers in Rembang, Central Java, from which samples were selected using proportional stratified random sampling, resulting in 312 teachers as research participants. Data were collected through a structured questionnaire and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that academic, collaborative, and clinical supervision have significant positive effects on teacher competence. Teacher competence, in turn, significantly enhances teacher well-being and performance, while well-being also directly contributes to improved performance. Furthermore, competence and well-being function as significant mediators, including a serial mediation pathway linking supervision to sustainable teacher performance. These findings demonstrate that the impact of supervision on performance is primarily indirect, operating through the development of professional capacity and psychological resources. This study contributes theoretically by advancing a care-based paradigm of supervision and provides practical implications for designing supervision policies that integrate pedagogical competence, emotional support, and teacher well-being as foundations for long-term performance.